Pandemia do COVID-19 e as possibilidades de ressignificação das atividades de gestão no ensino superior: relato de experiência - Moura Ferreira, Glaucirene Siebra; Vasconcelos, Lourdes Claudenia Aguiar; Ferreira, Francisco Ivanildo Sales; Oliveira, Paciolo Montini Costa; Alexandre de Paula, Paulo Henrique (Revista Enfermagem Atual In Derme, 2020)
Objective: It aims to report the management experience and the possibilities of reinventing academic activities due to the pandemic. To ensure the safety of students and teachers, all face-to-face activities were suspended, following the recommendations of health authorities to maintain social isolation. Method: This is a descriptive study, an experience report, referring to management activities in higher education at a college in the interior of Ceará. The study was carried out during the first semester of 2020. Results: The initial moment was uncertain due to the gloomy scenario that was presented. For the development of academic activities, in the midst of the new pandemic context, it was necessary to follow three steps: 1. Scenario analysis - In the scenario analysis, an understanding of the new reality that was abruptly established that reached the normal development of academic activities scheduled for the 2020.1 semester. 2. Planning - so that, in a crystalline way, we could see the possibilities for a resumption of activities. For this, a virtual technological resource was used for the space for proposing ideas, as well as for defining the necessary points that should be considered in the planning. 3. As advances in the development of remote activities progressed, new demands arose, such as evaluations, internet access, weak connection, emotional aspects, among others, which generated the need to revisit the previous steps, as indicated arrows in opposite directions, to readjust the steps. Conclusion: in the pandemic period, they reveal the possibility of finding new opportunities in carrying out the teaching-learning process. To this end, it is necessary to promote similar initiatives giving an opportunity for the ability to reinvent teachers and students as protagonists in the search for knowledge.